Improving the Self-concept of Women Commercial Sex Workers with Group Counseling Solution-focused Brief Counseling (SFBC) Approach - Netrawati, Netrawati; Syukur, Yarmis; Setiawan, Arif (Sawwa: Jurnal Studi Gender, 2023)
This study underscores the critical need for mental health intervention among commercial sex workers undergoing rehabilitation, focusing on gender issues, particularly women choosing alternative paths in this field. The psychological challenges linked to their identity as female sex workers require the identification and enhancement of their self-concept. The research evaluates the effectiveness of the Solution-focused Brief Counseling (SFBC) approach in fortifying the self-concept of women involved in commercial sex work through group counseling services. Conducted at the Andam Dewi rehabilitation center in Solok with 21 female participants, the study adopts a quasi-experimental design. Results affirm the efficacy of SFBC, highlighting its potential to improve women’s self-concept in this specific context. This study contributes to an underexplored domain, urging counselors at rehabilitation centers to embrace group counseling services and SFBC to enhance the self-concept of women engaged in commercial sex work.